The Effect of the Zimmerman Model on Achievement and Curiosity Among Third-year Students in the Department of Physics in the Curriculum Course (Journal of the College of Basic Education, 2026)
The present study aimed to explore the effect of the Zimmerman model on academic achievement and curiosity among third-year physics students in the curriculum course. To achieve this goal, the researcher formulated two null hypotheses and adopted a quasi-experimental design consisting of two groups (experimental and control) with two post-tests. The study sample consisted of 66 evening-class students from the third year of the Department of Physics for the academic year 2024–2025 (first semester). The students were randomly assigned into two equal groups: Group (A) with 33 students representing the experimental group taught according to the Zimmerman model, and Group (B) with 33 students representing the control group that received instruction using traditional methods. The researcher ensured the equivalence of the two groups across several variables and specified the instructional content to cover the first three chapters of the curriculum and teaching methods textbook. Additionally, 240 behavioral objectives were prepared to guide the experimental teaching process. The researcher also developed two post-tests: one to measure achievement and another to measure curiosity. The validity and reliability of these tests were verified, along with calculating difficulty indices, discrimination power, and the effectiveness of distractors using appropriate statistical formulas. After collecting and statistically analyzing the data using the t-test, the results revealed that the experimental group taught with the Zimmerman model outperformed the control group taught by traditional methods in both academic achievement and curiosity. Based on these findings, the researcher drew several conclusions and presented a set of recommendations and suggestions to enhance the educational process.